Emerging Signal Regulating Potential of Genistein Against Alzheimer’s Disease: A Promising Molecule of Interest - Uddin, Md. Sahab; Kabir, Md. Tanvir (Frontiers in Cell and Developmental Biology, 2019)
Alzheimer’s disease (AD) is a progressive, irreversible brain disorder characterized by pathological aggregation of the amyloid-β peptide (Aβ) and tau protein; both of these are toxic to neurons. Currently, natural products are regarded as an alternative approach to discover novel multipotent drugs against AD. Dietary soy isoflavone genistein is one of the examples of such agents that occurs naturally and is known to exert a number of beneficial health effects. It has been observed that genistein has the capacity to improve the impairments triggered by Aβ and also it possesses the antioxidant potential to scavenge the AD-mediated generation of free radicals. Furthermore, genistein can interact directly with the targeted signaling proteins and also can stabilize their activity to combat AD. In order to advance the development of AD treatment, a better comprehension of the direct interactions of target proteins and genistein might prove beneficial. Therefore, this article focuses on the therapeutic effects and molecular targets of genistein, which has been found to target directly the Aβ and tau to control the intracellular signaling pathways responsible for neurons death in the AD brain.